Jordan : Restructuring Public Expenditures and Protecting the Poor - Ahmad, Ehtisham (IMF Working Papers; Working Paper ;, 1991)
In Jordan, a system of general food subsidies became untenable in budgetary terms, with a sharp devaluation of the dinar in the late 1980s. A shift from a general subsidy system to limited rations would greatly reduce budgetary costs and minimize adverse effects on the poor. To reduce subsidies, the authorities had taken measures, during the course of 1990, consistent with the measures suggested. To complete the safety net, a system of self-targeting public works is suggested; a reform of the social security system might also be needed in view of the increased unemployment resulting from the recent Middle East crisis.